2015
DOI: 10.1182/blood-2015-03-633537
|View full text |Cite
|
Sign up to set email alerts
|

SF3B1 mutation identifies a distinct subset of myelodysplastic syndrome with ring sideroblasts

Abstract: Key Points• In MDS with ring sideroblasts, SF3B1 mutation defines a homogeneous subgroup with isolated erythroid dysplasia and favorable prognosis.• MDS with ring sideroblasts and wild-type SF3B1 is mainly characterized by multilineage dysplasia and unfavorable prognosis.Refractory anemia with ring sideroblasts (RARS) is a myelodysplastic syndrome (MDS) characterized by isolated erythroid dysplasia and 15% or more bone marrow ring sideroblasts. Ring sideroblasts are found also in other MDS subtypes, such as re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

22
261
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 379 publications
(290 citation statements)
references
References 42 publications
22
261
0
7
Order By: Relevance
“…Alterations in alternative splicing events lead to the production of pro-tumorigenic isoforms that have been linked to various steps of tumorigenesis, including proliferation, apoptosis, invasion, metabolism, angiogenesis, DNA damage, or even drug resistance and immune response. Malcovati et al 2011Malcovati et al , 2015Papaemmanuil et al 2011Papaemmanuil et al , 2013Wang et al 2011;Yoshida et al 2011;Bejar et al 2012;Damm et al 2012;Makishima et al 2012;Patnaik et al 2012;Visconte et al 2012;Walter et al 2013;Shirai et Yoshida et al 2011;Bejar et al 2012;Damm et al 2012;Makishima et al 2012;Thol et al 2012;Papaemmanuil et al 2013 MDS Yoshida et al 2011;Bejar et al 2012;Damm et al 2012;Graubert et al 2012;…”
Section: Srsf2-serine/arginine-rich Splicing Factormentioning
confidence: 99%
“…Alterations in alternative splicing events lead to the production of pro-tumorigenic isoforms that have been linked to various steps of tumorigenesis, including proliferation, apoptosis, invasion, metabolism, angiogenesis, DNA damage, or even drug resistance and immune response. Malcovati et al 2011Malcovati et al , 2015Papaemmanuil et al 2011Papaemmanuil et al , 2013Wang et al 2011;Yoshida et al 2011;Bejar et al 2012;Damm et al 2012;Makishima et al 2012;Patnaik et al 2012;Visconte et al 2012;Walter et al 2013;Shirai et Yoshida et al 2011;Bejar et al 2012;Damm et al 2012;Makishima et al 2012;Thol et al 2012;Papaemmanuil et al 2013 MDS Yoshida et al 2011;Bejar et al 2012;Damm et al 2012;Graubert et al 2012;…”
Section: Srsf2-serine/arginine-rich Splicing Factormentioning
confidence: 99%
“…8,11,12 SF3B1 was the first spliceosome family member to be implicated, and is mutated in up to 80% of MDS cases with ringed sideroblasts. 6,15 Splicing factor mutations are heterozygous and generally mutually exclusive of one another, suggesting that cells cannot tolerate two mutations or, alternatively, that these changes have a redundant role in disease pathogenesis. The spliceosome functions to mediate intron excision and exon ligation in the generation of mature messenger RNA molecules.…”
Section: Splicing Factorsmentioning
confidence: 99%
“…Clonal analysis based on the variant allele frequency of SF3B1 and other co-existing mutations revealed that mutations in SF3B1 are present in the dominant clone in most cases. Interestingly, the percentage of BM RS is highly correlated with SF3B1 mutant allele burden [4,[6][7][8], which strongly suggests that mutant SF3B1 directly or indirectly contributes to the formation of RS. In fact, SF3B1 mutations have a high positive predictive value for disease phenotype with RS of 97.7%, whereas the absence of these mutations has an equivalent negative prediction value [7].…”
Section: Genetic Profiles Of Rars and Mds/mpn-rs-t And Their Impact Omentioning
confidence: 95%
“…For example, Malcovati et al studied the influence of SF3B1 mutations on outcome in 293 patients with myeloid neoplasms with 1% or more RS [6]. In this cohort, SF3B1 mutations were detected in 129 of 159 patients (81%) with RARS or RCMD-RS, and multivariate analysis demonstrated that patients with SF3B1 mutations had significantly better overall survival [hazard ratio (HR) 0.37] and lower cumulative incidence of disease progression (HR 0.31).…”
Section: Genetic Profiles Of Rars and Mds/mpn-rs-t And Their Impact Omentioning
confidence: 99%